2019
DOI: 10.21873/invivo.11526
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Amyotrophic Lateral Sclerosis in SOD1G93AMice by M2Microglia from Transplanted Marrow

Abstract: Background/Aim: The cause of fatal neuromuscular amyotrophic lateral sclerosis (ALS) is not known. Materials and Methods: Ninety-day-old superoxidedismutase-1 G93A (SOD1 G93A) mice demonstrating level 1 paralysis, received 9.0 Gy total body irradiation (TBI) from a cesium source at 340 cGy per minute, and intravenous transplantation with 1×10 6 C57BL/6 green fluorescent protein (GFP)+ donor bone marrow cells. Results: Paralysis-free survival was prolonged in TBI and bone marrow-transplanted SOD1 G93A mice from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…However, increased PDGF-C signaling appears to be associated with BSCB disruption in ALS (Liebner et al, 2008), even if PDGFR-α signaling is actually necessary for the survival of these cells (Kisler et al, 2017). Recently, microglial activation, alone or together with peripheral immune cells contribution, has been hypothesized to be involved in the opening of the BSCB (Puentes et al, 2016;Frakes et al, 2017;Epperly et al, 2019). We have demonstrated that chemogenetic control of MN firing can bidirectionally modulate BSCB integrity: Increased firing reduces BSCB disruption, whereas neuronal inactivation worsens it.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased PDGF-C signaling appears to be associated with BSCB disruption in ALS (Liebner et al, 2008), even if PDGFR-α signaling is actually necessary for the survival of these cells (Kisler et al, 2017). Recently, microglial activation, alone or together with peripheral immune cells contribution, has been hypothesized to be involved in the opening of the BSCB (Puentes et al, 2016;Frakes et al, 2017;Epperly et al, 2019). We have demonstrated that chemogenetic control of MN firing can bidirectionally modulate BSCB integrity: Increased firing reduces BSCB disruption, whereas neuronal inactivation worsens it.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly demonstrated that MBP selectively downregulated M1 microglia/macrophage polarization without affecting the increased state of M2 microglia/macrophage polarization in G93A mice even after post-onset administration ( Figure 2 ). Furthermore, it has been reported that M2 microglia/macrophages from transplanted donor marrow delayed onset motor dysfunction in G93A mice [ 36 ]. These results suggest that the ability of MBP to not only maintain the neuroprotective M2 microglia/macrophage polarization but also to prevent the neurotoxic M1 microglia/macrophage polarization could be involved in improving the motor neuron loss and disease progression of G93A mice.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be partially explained by the ability of misfolded SOD1 to act as a damage-associated molecular pattern activating TLR receptors [44,45]. SOD1 G93A mice exhibit an improved hematopoiesis compared to mice expressing wild type SOD1, suggesting a specific effect of mutant SOD1 on hematopoietic progenitors [46]. In addition, other factors produced by motor neurons upon damage may potentially induce myeloid and microglial cell attraction and proliferation, including CSF1, MCP1, and ATP, among others [47,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%